Refusal of exequatur by a French court of a foreign judgment rendered by a non-competent judge: The «Nemagon» case of Nicaragua - Torrez Peralta, William (CUADERNOS DE DERECHO TRANSNACIONAL, 2024)
This article analyzes the denial of an application for exequatur by a French Court of a final Nicaraguan judicial decision, based on the lack of jurisdiction of the Nicaraguan Courts. The lack of jurisdiction of the Nicaraguan Court arises from the fact that the legislator introduced the doctrine of forum non conveniens in the Special Law 364/2000, approved to protect the persons who were harmed by the pesticide called «nemagon». This law was intended to respond to the numerous claims and to compensate the damages caused to the health of agricultural workers who had worked with this pesticide for years in banana plantations in Nicaragua. The result was the opposite of what was desired. The excesses of the legislator in adopting the thesis of forum non conveniens caused the judge who had heard the declaratory proceeding in Nicaragua to be considered incompetent by the French Court of exequatur.Keywords: Comparative law, foreign execution, forum non conveniens, Nicaragua, France.
Keywords: Comparative law; foreign execution; forum non conveniens; Nicaragua; France